Study on the effect of morphological changes of bridge piers on water movement properties - Xianqi Zhang (IWA Publishing, 2021)
The different shapes of bridge piers across rivers have a great influence on the river water movement, and the study of the influence of pier morphology changes on the water movement characteristics is of great value for bridge design and river flooding. The hydrodynamic model can effectively simulate and predict the changes of river flow patterns, which can provide scientific data support for river management. This paper constructs a hydrodynamic model based on MIKE21 and applies it to the numerical simulation of river hydrodynamics in the lower reaches of the Yellow River, taking elliptical piers as an example, and simulates the effect of the change of pier morphology on the flow velocity, water level and flow field of the river. The results show that the effect of elliptical pier morphology on the flow characteristics of the river channel is significant; under the same flow rate, the congestion value of the pier at the maximum axis ratio is 1.65 times the minimum axis ratio, and the larger the axis ratio, the more serious the congestion; the difference in flow velocity at the maximum axis ratio can reach 2.33 times the minimum axis ratio. HIGHLIGHTS This paper uses MIKE21 numerical simulation to analyze and study the changes in river congestion and flow patterns caused by bridge construction, and to provide more practical simulation data for the construction of cross-river bridges.; The Nash efficiency coefficient of 0.94 is highly accurate in the model validation and evaluation.;